Risk factors of anemia among pregnant women in community health center (Puskesmas) Singgani and Puskesmas Tipo Palu - Arum Diah Pusporini; Andi Ummu Salmah; Atjo Wahyu; Arifin Seweng; Apik Indarty; Suriah; Rosmala Nur; Aminuddin Syam; Mahfudz (Elsevier, 2021)
Objective: The aim of this study is to describe the risk factors of anemia among pregnant women. Method: We used an observational analytic study with a matched case-control study design. The sampling method used in this study is a simple random sampling technique. The sample size in this study is 138 samples that consist of 46 cases and 92 controls. The data obtained from patient medical records and analyzed statistically using the chi-square test. Results: Nutritional status is a risk factor of anemia among pregnant women in Community Health Center (Puskesmas) Singgani and Puskesmas Tipo. The risk of pregnant women with chronic energy deficiency (CED) developing anemia is higher in Puskesmas Singgani compared to in Puskesmas Tipo. Conclusion: Prevention can be done by counseling the bride and groom about pregnancy preparation and counseling the pregnant women to pay attention to the nutritional intake, particularly the consumption of folic acid supplements and iron.